2020
DOI: 10.1590/1806-9282.66.5.583
|View full text |Cite
|
Sign up to set email alerts
|

Multiple lidocaine infusions for relief of neuropathic pain: systematic review and meta-analysis

Abstract: The information provided through this project must be assessed and criticized by the physician responsible for the conduct that will be adopted, depending on the conditions and the clinical status of each patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 12 publications
(15 reference statements)
0
5
0
Order By: Relevance
“…Still, multiple lidocaine infusions of 3 mg/kg and 240 mg in chronic neuropathic pain and fibromyalgia over a period of once a week for 4 weeks have not been shown to have persistent benefits at 4 weeks and 8 weeks. [17,27,30,31]…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Still, multiple lidocaine infusions of 3 mg/kg and 240 mg in chronic neuropathic pain and fibromyalgia over a period of once a week for 4 weeks have not been shown to have persistent benefits at 4 weeks and 8 weeks. [17,27,30,31]…”
Section: Discussionmentioning
confidence: 99%
“…Still, multiple lidocaine infusions of 3 mg/kg and 240 mg in chronic neuropathic pain and fibromyalgia over a period of once a week for 4 weeks have not been shown to have persistent benefits at 4 weeks and 8 weeks. [17,27,30,31] In 1 previous study, the analgesic duration of 5 mg/kg lidocaine infusion was 6 hours longer than placebo, and some study participants reported a duration of analgesic effect longer than 7 days. [19] Tremont-Lukats et al [32] reported that a 5 mg/kg of lidocaine infusion for 6 hours was more effective than 1 or 3 mg/ kg to treat neuropathic pain.…”
Section: Effect Of Systemic Lidocaine and Its Dosagementioning
confidence: 99%
See 3 more Smart Citations